Effects of chronic betaine supplementation on exercise performance: Systematic review and meta-analysis - Zawieja, E.; Machek, S.; Zanchi, N. E.; Cholewa, J.; Wozniewicz, M. (Journal of Sports Sciences, 2024)
Betaine supplementation, a dietary practice that possesses potential effects on exercise performance, has undergone extensive study. This study aimed to systematically review and meta-analyse betaine supplementation`s effects on exercise performance. We searched PubMed, Web of Science, Scopus, and Google Scholar, focusing on studies comparing chronic betaine to a placebo in healthy humans aged 15-60 years, measuring exercise outcomes. Studies with acute betaine supplementation, no control group, or animals were excluded. Quality assessment was done using the Cochrane Risk of Bias Tool, and a random-effects model was employed for the meta-analysis. The review included 17 studies with 317 participants (21% female). The results revealed a significant effect size of 0.47 (95% CI 0.04 to 0.89) for maximal strength (1RM, 3RM, maximal isokinetic or isometric force), particularly in the lower body (SMD: 0.49, 95% CI 0.01 to 0.98). No significant effects were found for upper body strength, cycling sprint power, bench press throws power, or muscular endurance. However, vertical jumping performance improved significantly (SMD: 0.36, 95% CI 0.03 to 0.69) after excluding a low-quality study. In conclusion, betaine supplementation for at least 7 days significantly enhances muscular strength, especially lower body strength, and shows potential in improving vertical jumping performance.